2015
DOI: 10.7883/yoken.jjid.2014.181
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence Survey of Zoonoses in Extremadura, Southwestern Spain, 2002–2003

Abstract: SUMMARY: Our aims were to determine the seroprevalence rates for the most common types of zoonosis among the population of Extremadura (southwestern Spain) and to identify the associated risk factors. We conducted a seroepidemiological survey to collect information on family background and the habits of people residing in Extremadura between 2002 and 2003. Antibodies to Brucella were determined by Rose Bengal staining and a standard tube agglutination test; a titer of 1/80 was considered to be positive. Antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Several studies have investigated the role of ticks in the transmission of Brucella species. One study in Spain found that ticks collected from livestock were positive for Brucella DNA, suggesting their potential role as vectors for brucellosis transmission [ 73 ]. Similarly, another study conducted in Iran detected Brucella DNA in ticks collected from sheep and goats [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have investigated the role of ticks in the transmission of Brucella species. One study in Spain found that ticks collected from livestock were positive for Brucella DNA, suggesting their potential role as vectors for brucellosis transmission [ 73 ]. Similarly, another study conducted in Iran detected Brucella DNA in ticks collected from sheep and goats [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dear Editor: In a previous issue of the Japanese Journal of Infectious Diseases, Asencio et al carried out a study on the seroprevalence, and the risk factors associated with, 5 major zoonotic diseases namely brucellosis, echinococcosis, spotted fever, leishmaniasis, and toxoplasmosis, in the Spanish region of Extremadura (1). Despite their comprehensive study, and the limitations that the authors recognized in their paper, several further remarks should be taken into account.…”
Section: Survey Of Zoonoses In Extremadura Spainmentioning
confidence: 99%
“…Independent risk factors for brucellosis found were younger age, male gender, profession and contact with animals and consumption of contaminated fresh cheese. Brucellosis were more prevalent in rural areas associated with cheese consumption (Asencio et al, 2014). Rates of Brucella in human in the province that makes cheese with raw milk is the double as that use pasteurized milk (Celebi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%